Awareness and practice of care bundles for prevention of healthcare-associated infections in critical care units of a tertiary care hospital. - Amatya, Bishwo Ram; Singh, Priyanka; Pokharel, Sujita; Gurung, Sapana; Sharma, Bhagwati; Khatri, Sushila; Shrestha, Shova (Journal of Nepalese Society of Critical Care Medicine, 2025)
Background and aims: Healthcare-associated infection is infection acquired by patients in a hospital or health care facility that are not present at the time of admission. Care bundles are evidence-based practices that improve patient outcomes when implemented collectively. Since implementation of care bundle in resource-limited settings remain a challenge, this study was planned with the aim of exploring its awareness and practice among health care professionals working in critical care units.Methods: A population and provider based online observational survey was conducted in six different critical care units with 43 total ICU beds of a tertiary care hospital involving 95 health care workers during one month period. Google form questionnaire was used to collect responses. Awareness and practice score was categorized into excellent, good, average and poor. Excellent and good score were labeled as satisfactory whereas average and poor score were labeled as unsatisfactory.Results: Maximum participation was from registered nurses (57.89%) with 76.87 % of them having less than one year of working experience and only 10.57% having training on IPC. There was excellent awareness of VAP (88.42%) and CLABSI bundles (83.15%) with good awareness of CAUTI (77.89%) and SSI bundles (67.36%). However, practice of VAP (53.37%), CLABSI (55.69%), CAUTI (59.45%) and SSI (46.87%) bundles were only average.Conclusion: Participants having satisfactory awareness had unsatisfactory and inadequate practice of care bundles indicating poor adherence, compliance and implementation requiring adequate training of infection prevention and control, protocolized checklists and monitoring of best practices in ICU.